Evaluation of a Community-based Approach to Strengthen Retention in Early Childhood Home Visiting - Folger, Alonzo T. (Prev Sci, 2016)
Home visiting (HV) is a strategy for delivering services designed to promote positive parenting and prevent exposure to toxic stress during a critical period of child development. Home visiting programs are voluntary and family engagement and retention in service can influence outcomes. Most participants receive less home visits and for a shorter time than prescribed by evidence-based models. The purpose of this study was to evaluate community-based enrichment of HV (CBE-HV), an approach that was developed and implemented to increase engagement and retention in HV. CBE-HV strategies included (1) community engagement, (2) ancillary supports for families in HV, and (3) enhancements to a HV program. A retrospective, quasi-experimental study was conducted to estimate the effect of CBE-HV on the retention of families in a HV program. Comparisons of study participants were made post-implementation of CBE-HV (n=2,191) and over time (n=3,786)—pre versus post CBE-HV implementation in the study communities. The CBE-HV effect was statistically significant and protective (hazards ratio [HR] 0.77, 95% confidence interval [CI]: 0.67, 0.88), indicating that attrition from HV was 23% less in the CBE-HV group relative to the post-implementation comparison group. In the temporal comparison of study communities, CBE-HV was also associated with a significantly lower risk of HV attrition (HR: 0.71, 95% CI: 0.56, 0.89). The study demonstrated that CBE-HV is a promising approach to achieve stronger retention and engagement in HV. Further research is needed to identify the components of CBE-HV approaches that are most effective.